2011
DOI: 10.1016/j.jtcvs.2010.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative high-dose atorvastatin for prevention of atrial fibrillation after cardiac surgery: A randomized controlled trial

Abstract: High-dose atorvastatin for 7 days before cardiac surgery conferred a nonsignificant reduction in postoperative atrial fibrillation when compared with a low-dose regimen. A larger study would be necessary to confirm the beneficial effect of high-dose statins in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 21 publications
0
20
0
2
Order By: Relevance
“…Atorvastatin 40 mg/day for 7 days before surgery had the largest effect in preventing PNAF, with an absolute risk reduction of PNAF compared with placebo of 22·0% ( P = 0·017) . No differences were found between doses of atorvastatin of 80 and 40 mg/day .…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Atorvastatin 40 mg/day for 7 days before surgery had the largest effect in preventing PNAF, with an absolute risk reduction of PNAF compared with placebo of 22·0% ( P = 0·017) . No differences were found between doses of atorvastatin of 80 and 40 mg/day .…”
Section: Resultsmentioning
confidence: 89%
“…Fifteen cohort studies and six RCTs evaluated the effect of preoperative and postoperative statins on preventing PNAF. Of the 15 cohort studies, ten studies found that statins prevented PNAF .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trials with different doses of atorvastatin were limited and with significant heterogeneity in the study populations, so subgroup analysis according to different doses was not performed in our meta-analysis. A previous meta-analysis [32] even came to the conclusion that the preventive effect of atorvastatin on AF may be more significant at a lower dose (10–40 mg/day), while a recent study [33] on patients undergoing cardiac surgery suggested that the preventive effect of atorvastatin on postoperative AF was not dose-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…The final search identified 32 trials 30 & , 31,32 && , [33][34][35] that fulfilled the inclusion criteria. We conducted text searches with the terms 'statin' and 'atrial fibrillation'.…”
Section: Methodsmentioning
confidence: 99%